Effect of Charge on the Catalytic Activity of CO Oxidation by zeolite Supported Single Site Palladium: A Density Functional Study. Issue 28 (2nd October 2017) - Begum, Pakiza; Deka, Ramesh C.
Abstract: We have studied the oxidation of CO on palladium monomer in three oxidation states, viz. 0, +1 and +2, supported on FAU zeolite, using density functional theory. When metal complexes and clusters are attached to oxide or zeolite supports, they may well combine the industrial benefits of solid catalysts (heftiness for high temperature operation, absence of corrosiveness and comfort of separation from products) with the selectivity of soluble molecular catalysts. Further, single‐atom catalysts (SACs) with discrete and isolated metal atoms anchored to supports can perform as active centres having significant and unique performances, such as drastic cost‐reduction, notable catalytic activity and selectivity. CO oxidation has been extensively studied, as designing suitable catalysts is one of the foremost challenges in the field of catalytic research to remove poisonous carbon monoxide. CO oxidation over Pd n /FAU ( n =0, +1 and +2) have been investigated which elucidate the effect of cluster charge state on the catalytic activity. The conventional bimolecular Langmuir‐Hinshelwood mechanism with co‐adsorbed CO and O2 has been considered. Our calculations indicate that Pd 2+ /FAU displays better catalytic activity among the considered systems. This study is anticipated to provide useful information for the development of highly active catalyst for CO oxidation. Abstract : DFT study on CO (2CO + O2 → 2CO2 ) oxidation using traditional bimolecular Langmuir Hinshelwood mechanism. To elucidate the effect of charge on the catalytic activity of CO oxidation by zeolite supported single site Palladium, calculations have been carried out for three oxidation states: neutral (Pd 0 ) and cationic (Pd + and Pd 2+ ) systems of the monomer. The dicationic system (FAU/Pd 2+ ) is found to be the dominant catalytic system.